Thermoplastic elastomer material and preparation method thereof

By adding modified polyhedral oligosilsesquioxane and its derivative flame retardant synergist to the TPS material, the protective layer is formed, which solves the problem of poor flame retardancy of TPS materials, and achieves the effects of high flame retardancy, cracking and dripping.

CN119823517AActive Publication Date: 2025-04-15SHENZHEN WOER HEAT SHRINKABLE MATERIAL
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411992947.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-15
Estimated Expiration
2044-12-31

AI Technical Summary

Technical Problem

The existing TPS materials have poor flame retardancy and are limited in terms of high mechanical properties and crack resistance, making it difficult to meet the needs of high flame retardancy, crack resistance and drip resistance.

Method used

By adding modified polyhedral oligosilsesquioxane and its derivative flame retardant synergist, P-type flame retardant, N-type flame retardant and inorganic flame retardant to the thermoplastic elastomer material, a carbon layer, a ceramic barrier layer, a protective film or a thermally insulated coke layer is formed to enhance the flame retardant performance and drip-proof effect of the material.

Benefits of technology

It significantly improves the flame retardant and cracking resistance of the material, ensures that the material can prevent dripping during combustion, and isolates heat and oxygen transfer, reducing the release of combustible gases.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119823517A_ABST
    Figure CN119823517A_ABST
Patent Text Reader

Abstract

The thermoplastic elastomer material comprises PP (polypropylene), SEBS (styrene-ethylene-butylene-styrene), a plasticizer, a compatilizer, a P-series flame retardant, an N-series flame retardant, an inorganic flame retardant, modified polyhedral oligomeric silsesquioxane and a derivative flame-retardant synergist of the modified polyhedral oligomeric silsesquioxane. The modified polyhedral oligomeric silsesquioxane and the derivative flame-retardant synergist thereof contain boron, an annular structure R2 with the carbon hydrogen ratio larger than 1 and two inorganic silicon cage cores, and the structures form a carbon layer, a ceramic barrier layer, a protective film or a heat-insulation coke layer and other protective layers in the combustion process, so that the anti-dripping effect is greatly improved, and meanwhile, the anti-dripping effect is greatly improved. Heat and oxygen transfer is isolated, combustible gas release is reduced, and the flame retardant property of the material is remarkably improved under the combined action of multiple mechanisms. Furthermore, the flame-retardant synergist of the modified polyhedral oligomeric silsesquioxane and the derivative of the modified polyhedral oligomeric silsesquioxane is matched with the P-series flame retardant, the N-series flame retardant and the inorganic flame retardant to realize synergistic flame retardance, so that the flame retardance of the thermoplastic elastomer material is improved while the dosage of the flame retardant is reduced. The thermoplastic elastomer material provided by the invention is excellent in flame retardant property.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of materials, and in particular to a thermoplastic elastomer material and a preparation method thereof. Background Art

[0002] Polyhedral oligomeric silsesquioxane (POSS) is a special organic amorphous material. It is a polycyclic organic monomer composed of a silicon framework and its embedded oxygen atoms. It is an inorganic-organic hybrid nanomaterial. The inorganic silicon cage core in POSS decomposes under heat to form a dense ceramic barrier layer, which isolates the release of combustible gas and the entry of external heat into the interior, thereby delaying further decomposition of the material. POSS shows great application potential in the field of flame retardants.

[0003] Thermoplastic elastomer (TPS) material is mainly made of SEBS, white oil, PP, with certain plasticizers, antioxidants, etc. It has a wide hardness range, excellent hand feel, low temperature resistance, low price and excellent elasticity. There are many kinds of low-smoke, halogen-free flame-retardant TPS cable materials in the foreign market that can meet the flame-retardant requirements of UL wires. The comprehensive performance of low-smoke, halogen-free flame-retardant TPS cable materials produced domestically is far behind that of imported products. Due to the limitations of domestic flame-retardant technology, the development of TPS materials with high flame retardancy, high mechanical properties and crack resistance has not made significant progress. Therefore, it is very necessary to develop a halogen-free TPS material with high flame retardancy, crack resistance and drip resistance. Summary of the invention

[0004] In view of the above-mentioned deficiencies in the prior art, the present invention proposes a thermoplastic elastomer material, aiming to solve the problem of poor flame retardancy of the current TPS material.

[0005] The above object of the present invention is achieved through the following technical solutions:

[0006] In a first aspect, the present invention provides a thermoplastic elastomer material, wherein the raw materials of the thermoplastic elastomer material, measured in parts by weight, include:

[0007] PP 15-22 parts,

[0008] SEBS 20-30 parts,

[0009] 20-30 parts of plasticizer,

[0010] 3-8 parts of compatibilizer,

[0011] P series flame retardant 10-25 parts,

[0012] N series flame retardant 10-25 parts,

[0013] Inorganic flame retardant 10-15 parts,

[0014] 2-15 parts of modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist,

[0015] Wherein, the structure of the modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist is:

[0016]

[0017] Wherein, R is a non-reactive group, such as isobutyl, isooctyl, ethyl, cyclohexyl, cyclopentyl, or phenyl, and R1 is n-propyl or phenylene;

[0018] R2 is a cyclic structure with a carbon-to-hydrogen ratio greater than 1, including at least one of a benzofuran group and a polycyclic aromatic group.

[0019] In some embodiments of the present invention, the benzofuran group includes at least one of a benzofuran group and a dibenzofuran group;

[0020] And / or, the polycyclic aromatic group includes at least one of a naphthalene ring group, an anthracene ring group, a phenanthrene ring group, an acenaphthene ring group, a fluorene ring group and a perylene ring group.

[0021] In some embodiments of the present invention, the modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist is prepared by dehydration reaction of compound 1 and compound 2 under the action of a catalyst, and the reaction route is as follows:

[0022]

[0023] In some embodiments of the present invention, the molar ratio of compound 1 to compound 2 is 2:1.

[0024] In some embodiments of the present invention, the method for preparing the modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist comprises the following steps:

[0025] Dissolving compound 1 in an organic solvent, adding an aqueous solution of compound 2 under the action of a catalyst, performing a catalytic reaction, and then washing and drying to obtain the modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist;

[0026] Wherein, the organic solvent includes at least one of alcohols, aromatic hydrocarbons, aliphatic hydrocarbons, alicyclic hydrocarbons, ethers, ketones and diol derivatives;

[0027] The catalyst includes at least one of an acidic catalyst, a metal catalyst, and a basic catalyst.

[0028] In some embodiments of the present invention, the raw materials of the thermoplastic elastomer material include, by weight:

[0029] PP 15-22 parts,

[0030] SEBS 20-30 parts,

[0031] 20-30 parts of plasticizer,

[0032] 3-8 parts of compatibilizer,

[0033] P series flame retardant 10-15 parts,

[0034] N series flame retardant 10-15 parts,

[0035] Inorganic flame retardant 10-12 parts,

[0036] 2-15 parts of modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist.

[0037] In some embodiments of the present invention, the plasticizer includes at least one of white oil, cyclohexane oil, and paraffin oil.

[0038] In some embodiments of the present invention, the compatibilizer includes at least one of PE grafted maleic anhydride, POE grafted maleic anhydride, PP grafted maleic anhydride, and EMA grafted maleic anhydride.

[0039] In some embodiments of the present invention, the P series flame retardant includes an inorganic phosphorus flame retardant or an organic phosphorus flame retardant, wherein the inorganic phosphorus flame retardant includes at least one of red phosphorus, phosphate, and polyphosphate; the organic phosphorus flame retardant includes at least one of phosphate ester, phosphite, and phosphine oxide; and / or the N series flame retardant includes at least one of melamine urate, melamine phosphate, and melamine inorganic acid salt.

[0040] In some embodiments of the present invention, the inorganic flame retardant includes at least one of magnesium hydroxide, aluminum hydroxide, and calcium carbonate.

[0041] In some embodiments of the present invention, the raw material of the thermoplastic elastomer material also includes at least one of a lubricant, an antioxidant, and a light stabilizer; wherein, the raw materials are calculated by weight, the lubricant is 0.2-1 part, the antioxidant is 0.5-2 parts, and the light stabilizer is 0.2-1 part.

[0042] In a second aspect, the present invention provides a method for preparing the above-mentioned thermoplastic elastomer material, comprising the following steps: mixing the raw materials uniformly, extruding and granulating through an extruder to obtain a granular material, namely the thermoplastic elastomer material.

[0043] In some embodiments of the present invention, the raw material further includes at least one of a lubricant, an antioxidant, and a light stabilizer.

[0044] The thermoplastic elastomer material of the present invention comprises PP, SEBS, a plasticizer, a compatibilizer, a P-series flame retardant, an N-series flame retardant, an inorganic flame retardant and a flame retardant synergist of modified polyhedral oligomeric silsesquioxane and its derivatives. Since the modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist contains boron, a ring structure R2 with a carbon-to-hydrogen ratio greater than 1, and two inorganic silicon cage cores, the boron element forms boric acid during the combustion process, and the boric acid dehydrates and carbonizes the surface of the material to form a carbon layer; the two inorganic silicon cage cores decompose under heat to form a dense ceramic barrier layer, which isolates the release of combustible gas and the entry of external heat into the interior; the ring structure R2 with a carbon-to-hydrogen ratio greater than 1 has a higher carbon-to-hydrogen ratio, and the benzofuran group and the polycyclic aromatic group contain a large amount of carbon elements. A large amount of carbon elements will form a glassy protective film or an insulating coke layer during the combustion process. These protective films or coke layers can isolate the air, prevent the transfer of heat, and reduce the release of combustible gases. These structures form protective layers such as carbon layers, ceramic barrier layers, protective films or insulating coke layers during the combustion process, which greatly improve the anti-drip effect. At the same time, they isolate heat and oxygen transfer and reduce the release of combustible gases. The combined effect of multiple mechanisms significantly improves the flame retardant properties of the material. Modified POSS and its derivative flame retardant synergist, P series flame retardant, N series flame retardant and inorganic flame retardant are used as the main flame retardant components of thermoplastic elastomer materials. The components cooperate and work synergistically with each other. During the combustion process, Si element and C element in the R2 group can react rapidly to generate a large number of Si-C bonds. At the same time, B element can form a glass film on the surface of the thermoplastic elastomer material, and the generated boric acid can rapidly dehydrate the polymer to produce a carbon layer. The B element in the modified POSS and its derivative synergistic flame retardant can also coordinate with the P element in the system to produce a synergistic effect, thereby improving the flame retardant effect. By adding modified POSS and its derivative synergistic flame retardant and P series and N series flame retardant The flame retardants work synergistically to quickly produce a harder carbon layer to prevent the thermoplastic elastomer from burning and dripping, and isolate the air to improve the flame retardancy of the thermoplastic elastomer. Among them, the P series flame retardant provides an acid source, the N series flame retardant provides a gas source, and the modified POSS and its derivative synergistic flame retardant provide a rich carbon source, so that the P series flame retardant and the N series flame retardant have stronger flame retardancy. Furthermore, the modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist cooperates with the inorganic flame retardant to synergistically flame retardant, so that the prepared thermoplastic elastomer material can ensure the original good processing performance, elasticity and flame retardant performance of the thermoplastic elastomer, and improve the anti-cracking performance, flame retardancy and physical and mechanical properties of the thermoplastic elastomer material. The thermoplastic elastomer material provided by the present invention has excellent flame retardancy and crack resistance and can prevent dripping during combustion. The modified POSS and its derivative flame retardant synergist are in the form of a colorless viscous liquid, which has little effect on the performance of the thermoplastic elastomer material when added to the thermoplastic elastomer material, and a thermoplastic elastomer material with excellent flame retardancy can be obtained without a very high addition amount. BRIEF DESCRIPTION OF THE DRAWINGS

[0045] Figure 1 The molecular structure diagram of the modified POSS flame retardant synergist 1 of the present invention;

[0046] Figure 2 This is a molecular structure diagram of the modified POSS flame retardant synergist 2 of the present invention. DETAILED DESCRIPTION

[0047] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. It should be understood that the following embodiments are only used to explain the present invention and are not used to limit the present invention.

[0048] Unless defined otherwise, all technical and scientific terms used herein have the common meaning in the art to which the claimed subject matter belongs.

[0049] PP: Polypropylene is a semi-crystalline thermoplastic polymer made from propylene monomer through addition polymerization. Polypropylene has the characteristics of lightness, wear resistance, antibacterial and easy dyeing, and is widely used in fiber products such as clothing and blankets; it has good insulation properties and is used to manufacture refrigerators, washing machines, air conditioners, TV casings and parts; it has good chemical stability, heat resistance, transparency and mechanical properties, and is used to manufacture medical devices; it has good corrosion resistance, weather resistance and plasticity, and is used to manufacture construction and building materials products.

[0050] SEBS: Styrene Ethylene Butylene Styrene is a linear triblock copolymer with polystyrene as the terminal segment and ethylene-butene copolymer obtained by hydrogenating polybutadiene as the middle elastic block. SEBS has good stability and aging resistance because its molecular chain does not contain unsaturated double bonds, which makes it show excellent aging resistance in light oxygen and ozone environments.

[0051] Polyhedral oligomeric silsesquioxane (POSS) is a special organic amorphous material. It is a polycyclic organic monomer composed of a silicon framework and its embedded oxygen atoms. It is an inorganic-organic hybrid nanomaterial. The inorganic silicon cage core in POSS decomposes under heat to form a dense ceramic barrier layer, which isolates the release of combustible gas and the entry of external heat into the interior, thereby delaying further decomposition of the material. POSS shows great application potential in the field of flame retardants.

[0052] Thermoplastic elastomer (TPS) material is mainly made of SEBS, white oil, PP, with certain plasticizers, antioxidants, etc. It has a wide hardness range, excellent hand feel, low temperature resistance, low price and excellent elasticity. There are many kinds of low-smoke, halogen-free flame-retardant TPS cable materials in the foreign market that can meet the flame-retardant requirements of UL wires. The comprehensive performance of low-smoke, halogen-free flame-retardant TPS cable materials produced domestically is far behind that of imported products. Due to the limitations of domestic flame-retardant technology, the development of TPS materials with high flame retardancy, high mechanical properties and crack resistance has not made significant progress. Therefore, it is very necessary to develop a halogen-free TPS material with high flame retardancy, crack resistance and drip resistance.

[0053] In order to solve the above problems, the first aspect of the present invention provides a thermoplastic elastomer material. The raw materials of the thermoplastic elastomer material, measured in parts by weight, include:

[0054] PP 15-22 parts,

[0055] SEBS 20-30 parts,

[0056] 20-30 parts of plasticizer,

[0057] 3-8 parts of compatibilizer,

[0058] P series flame retardant 10-25 parts,

[0059] N series flame retardant 10-25 parts,

[0060] Inorganic flame retardant 10-15 parts,

[0061] 2-15 parts of modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist,

[0062] The structure of the modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist is:

[0063]

[0064] Wherein, R is a non-reactive group, such as isobutyl, isooctyl, ethyl, cyclohexyl, cyclopentyl, or phenyl, and R1 is n-propyl or phenylene;

[0065] R2 is a cyclic structure with a carbon-to-hydrogen ratio greater than 1, including at least one of a benzofuran group and a polycyclic aromatic group.

[0066] It can be understood that when R1 connected to Si in the inorganic silicon cage core is a phenylene group, since the phenylene group contains a benzene ring, the carbon-to-hydrogen ratio and the carbon content of the benzene ring are relatively high. When burned, it works together with the large amount of Si contained in the inorganic silicon cage core to further improve the flame retardant properties of the inorganic silicon cage core, thereby improving the flame retardant properties of the modified polyhedral oligomeric silsesquioxane flame retardant synergist.

[0067] The thermoplastic elastomer material of the present invention comprises PP, SEBS, a plasticizer, a compatibilizer, a P-series flame retardant, an N-series flame retardant, an inorganic flame retardant and a flame retardant synergist of modified polyhedral oligomeric silsesquioxane and its derivatives. Since the modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist contains boron, a ring structure R2 with a carbon-to-hydrogen ratio greater than 1, and two inorganic silicon cage cores, the boron element forms boric acid during the combustion process, and the boric acid dehydrates and carbonizes the surface of the material to form a carbon layer; the two inorganic silicon cage cores decompose under heat to form a dense ceramic barrier layer, which isolates the release of combustible gas and the entry of external heat into the interior; the ring structure R2 with a carbon-to-hydrogen ratio greater than 1 has a higher carbon-to-hydrogen ratio, and the benzofuran group and the polycyclic aromatic group contain a large amount of carbon elements. A large amount of carbon elements will form a glassy protective film or an insulating coke layer during the combustion process. These protective films or coke layers can isolate the air, prevent the transfer of heat, and reduce the release of combustible gases. These structures form protective layers such as carbon layers, ceramic barrier layers, protective films or insulating coke layers during the combustion process, which greatly improve the anti-drip effect. At the same time, they isolate heat and oxygen transfer and reduce the release of combustible gases. The combined effect of multiple mechanisms significantly improves the flame retardant properties of the material. Modified POSS and its derivative flame retardant synergist, P series flame retardant, N series flame retardant and inorganic flame retardant are used as the main flame retardant components of thermoplastic elastomer materials. The components cooperate and work synergistically with each other. During the combustion process, Si element and C element in the R2 group can react rapidly to generate a large number of Si-C bonds. At the same time, B element can form a glass film on the surface of the thermoplastic elastomer material, and the generated boric acid can rapidly dehydrate the polymer to produce a carbon layer. The B element in the modified POSS and its derivative synergistic flame retardant can also coordinate with the P element in the system to produce a synergistic effect, thereby improving the flame retardant effect. By adding modified POSS and its derivative synergistic flame retardant and P series and N series flame retardant The flame retardants work synergistically to quickly produce a harder carbon layer to prevent the thermoplastic elastomer from burning and dripping, and isolate the air to improve the flame retardancy of the thermoplastic elastomer. Among them, the P series flame retardant provides an acid source, the N series flame retardant provides a gas source, and the modified POSS and its derivative synergistic flame retardant provide a rich carbon source, so that the P series flame retardant and the N series flame retardant have stronger flame retardancy. Furthermore, the modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist cooperates with the inorganic flame retardant to synergistically flame retardant, so that the prepared thermoplastic elastomer material can ensure the original good processing performance, elasticity and flame retardant performance of the thermoplastic elastomer, and improve the anti-cracking performance, flame retardancy and physical and mechanical properties of the thermoplastic elastomer material. The thermoplastic elastomer material provided by the present invention has excellent flame retardancy and crack resistance and can prevent dripping during combustion. The modified POSS and its derivative flame retardant synergist are in the form of a colorless viscous liquid, which has little effect on the performance of the thermoplastic elastomer material when added to the thermoplastic elastomer material, and a thermoplastic elastomer material with excellent flame retardancy can be obtained without a very high addition amount.

[0068] Further, the benzofuran group includes at least one of a benzofuran group and a dibenzofuran group.

[0069] The carbon-to-hydrogen ratio and carbon content in phenyl are both high, which can slow down the spread of flames during combustion. When the flame is removed, it can quickly extinguish itself, reducing the duration and intensity of combustion. The furan group has a high carbon content and contains oxygen elements that do not participate in combustion. The combination of the two forms a benzofuran group or dibenzofuran group that has both a high carbon-to-hydrogen ratio and a low combustion element. The two work together to form a glass-like protective film or an insulating coke layer during the combustion process. These protective films or coke layers can isolate the air and prevent heat transfer, while reducing the content of combustibles and indirectly promoting carbonization.

[0070] In some embodiments, R2 is a benzofuranyl group.

[0071] In some embodiments, the polycyclic aromatic group includes at least one of a naphthalene ring group, an anthracene ring group, a phenanthrene ring group, an acenaphthene ring group, a fluorene ring group, and a perylene ring group.

[0072] The naphthalene ring group, anthracene ring group, phenanthrene ring group, acenaphthene ring group, fluorene ring group and perylene ring group have a relatively high carbon-hydrogen ratio and contain a large amount of carbon elements, which makes it easier to form a glass-like protective film or a heat-insulating coke layer when burned.

[0073] In some embodiments, R2 is a naphthyl ring group.

[0074] Furthermore, the modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist is prepared by dehydration reaction of compound 1 and compound 2 under the action of a catalyst, and the reaction route is as follows:

[0075]

[0076] Furthermore, in the above reaction process, the molar ratio of compound 1 to compound 2 is 2:1.

[0077] The spatial structure of compound 1 polyhedral oligomeric silsesquioxane is relatively large. In the reaction, it is necessary to ensure that compound 2 has a sufficiently small spatial steric hindrance so that it can react with compound 1 to obtain compound 3 modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist. During the reaction, each compound 2 is connected to two compounds 1, that is, the molar ratio of compound 1 to compound 2 is 2:1, which ensures sufficient space for compound 3 and achieves structural stability of compound 3. Compound 2 contains two hydroxyl groups, and the two hydroxyl groups of one compound 2 are respectively combined with one amino group in two compounds 1 to undergo a dehydration reaction to obtain compound 3. The overall reaction requires a single substance, is simple to operate, and is easy to implement.

[0078] In some embodiments, compound 1 is aminopropyl heptaisobutyl caged polysilsesquioxane.

[0079] In some embodiments, compound 1 is aminophenyl heptaisobutyl caged polysilsesquioxane.

[0080] In some embodiments, compound 2 is benzo[B]naphtho[2,3-D]furan-2-hydroxyboronic acid.

[0081] In some embodiments, compound 2 is dibenzofuran-4-boronic acid.

[0082] In some embodiments, the structural formula of compound 3 is:

[0083]

[0084] The following is designated as modified POSS flame retardant synergist 1.

[0085] In some embodiments, the structural formula of compound 3 is:

[0086]

[0087] The following is designated as modified POSS flame retardant synergist 2.

[0088] Furthermore, the preparation method of compound 3 comprises the following steps:

[0089] Compound 1 is dissolved in an organic solvent, and an aqueous solution of compound 2 is added under the action of a catalyst, and the mixture is subjected to a catalytic reaction, and then washed and dried to obtain compound 3;

[0090] Wherein, the organic solvent includes at least one of alcohols, aromatic hydrocarbons, aliphatic hydrocarbons, alicyclic hydrocarbons, ethers, ketones and diol derivatives;

[0091] The catalyst includes at least one of an acidic catalyst, a metal catalyst, and a basic catalyst.

[0092] In some embodiments, the catalyst is acetic acid.

[0093] In some embodiments, the solvent is ethanol.

[0094] Furthermore, the raw materials of the thermoplastic elastomer material include, by weight:

[0095] PP 15-22 parts,

[0096] SEBS 20-30 parts,

[0097] 20-30 parts of plasticizer,

[0098] 3-8 parts of compatibilizer,

[0099] P series flame retardant 10-15 parts,

[0100] N series flame retardant 10-15 parts,

[0101] Inorganic flame retardant 10-12 parts,

[0102] 2-15 parts of modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist.

[0103] Reducing the amount of P-series flame retardants, N-series flame retardants and inorganic flame retardants can further improve the mechanical properties of thermoplastic elastomer materials.

[0104] Furthermore, the plasticizer includes at least one of white oil, cyclohexane oil and paraffin oil.

[0105] Plasticizers are used to increase the fluidity of thermoplastic elastomers and improve the processing properties of thermoplastic elastomers.

[0106] In some embodiments, the plasticizer is preferably white oil.

[0107] Furthermore, the compatibilizer includes at least one of PE grafted maleic anhydride, POE grafted maleic anhydride, PP grafted maleic anhydride, and EMA grafted maleic anhydride.

[0108] The compatibilizer forms a bridge between the base resin and the flame retardant, improving their interfacial compatibility and adhesion, allowing the flame retardant to be more evenly dispersed in the matrix, thereby increasing the filling rate and flame retardant effect and improving the overall performance of the cable. The compatibilizer can also reduce incompatibility problems in the production process, thereby improving the production process and increasing production efficiency.

[0109] Furthermore, the P series flame retardant includes an inorganic phosphorus flame retardant or an organic phosphorus flame retardant, the inorganic phosphorus flame retardant includes at least one of red phosphorus, phosphate, and polyphosphate; the organic phosphorus flame retardant includes at least one of phosphate ester, phosphite, and phosphine oxide; and / or, the N series flame retardant includes at least one of melamine urate, melamine phosphate, and melamine inorganic acid salt.

[0110] It is understood that the phosphorus-based flame retardant includes, but is not limited to, aluminum hypophosphite, calcium hypophosphite, diethyl aluminum phosphite, methyl ethyl aluminum hypophosphite and phenyl aluminum hypophosphite.

[0111] In some embodiments, the P-based flame retardant is preferably aluminum diethylphosphinate.

[0112] In some embodiments, the N-based flame retardant is preferably melamine cyanurate.

[0113] Furthermore, the inorganic flame retardant includes at least one of magnesium hydroxide, aluminum hydroxide and calcium carbonate.

[0114] It is understood that inorganic flame retardants include but are not limited to magnesium hydroxide, aluminum hydroxide, and calcium carbonate.

[0115] In some embodiments, the inorganic flame retardant is preferably aluminum hydroxide.

[0116] Furthermore, the raw materials of the thermoplastic elastomer material also include at least one of a lubricant, an antioxidant, and a light stabilizer; wherein, the raw materials, in parts by weight, comprise 0.2-1 part of lubricant, 0.5-2 parts of antioxidant, and 0.2-1 part of light stabilizer.

[0117] In some embodiments, the antioxidant includes, but is not limited to, asymmetric hindered phenol antioxidants, aromatic amine antioxidants, thioether antioxidants, and phosphite antioxidants.

[0118] Hindered phenol antioxidants include, but are not limited to, antioxidant 1010 (pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate), BHT (2,6-di-tert-butyl-p-cresol), and antioxidant 1076 (β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate);

[0119] Aromatic amine antioxidants include, but are not limited to, diphenylamine, p-phenylenediamine, and dihydroquinoline and their derivatives or polymers, such as: Antioxidant 445 (4,4'-bis(α.α-dimethylbenzyl)diphenylamine);

[0120] Thioether antioxidants include, but are not limited to, DLTP (dilauryl thiodipropionate), DSTDP (distearyl thiodipropionate), and DSTP (octadecyl thiodipropionate);

[0121] Phosphite antioxidants include, but are not limited to, antioxidant 168 (tris[2.4-di-tert-butylphenyl]phosphite), antioxidant 618 (pentaerythritol distearyl diphosphite), and antioxidant 626 (bis[2.4-di-tert-butylphenyl]pentaerythritol diphosphite).

[0122] By adding antioxidants, the anti-oxidation and anti-aging properties of polymer materials are improved, and the service life of polymer materials is extended.

[0123] In some embodiments, the lubricant includes but is not limited to PTFE powder, zinc stearate, magnesium stearate, silicone, calcium stearate or ethylene bis stearamide. By adding the lubricant, it is beneficial to promote a more uniform mixing of various raw materials, improve the fluidity of the polymer resin, reduce the friction coefficient, make the surface of the product smoother, improve the processing efficiency, and improve the transparency and gloss of the plastic.

[0124] In some embodiments, light stabilizers include, but are not limited to, carbon black, zinc oxide, benzotriazoles, and triazines. By adding light stabilizers, multiple mechanisms are used to protect materials, including shielding or reflecting ultraviolet rays, absorbing ultraviolet rays and converting them into heat energy, quenching molecules or groups excited by ultraviolet rays, and capturing free radicals generated by photooxidation and reduction, thereby preventing photooxidation reactions, protecting polymer materials from the effects of light aging, and extending their service life.

[0125] In a second aspect, the present invention provides a method for preparing the above-mentioned thermoplastic elastomer material, comprising the following steps: uniformly mixing the raw materials, namely PP, SEBS, plasticizer, compatibilizer, P series flame retardant, N series flame retardant, inorganic flame retardant and modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist, extruding and granulating through an extruder to obtain a granular material, namely the thermoplastic elastomer material.

[0126] Furthermore, the raw material also includes at least one of a lubricant, an antioxidant, and a light stabilizer.

[0127] The content of the present invention is explained below through specific examples and data.

[0128] The information of the raw materials involved in the specific implementation is shown in Table 1:

[0129] Table 1 Information of raw materials of Examples and Comparative Examples

[0130]

[0131]

[0132] The thermoplastic polyurethane elastomer materials obtained in the above examples and comparative examples were injection molded or molded, and flame retardant grade, oxygen index, tensile strength, elongation at break, 110°C heat shock, 130°C heat shock, 150°C heat shock tests were performed. The test standards are as follows:

[0133] (1) Flame retardant grade test

[0134] In accordance with GB / T 5455-2014, the specimens are subjected to vertical burning grade test, the specimens are cut to the specified size and tested under conditions, and key parameters such as burning time limit and residual substances are monitored.

[0135] (2) Whether there is dripping when testing the flame retardancy level

[0136] Whether there is dripping when testing the flame retardancy level is tested according to the UL94 standard, the sample thickness is 3mm, and the test temperature is 23±2℃. The test is carried out using the UL94 vertical combustion test device of Jiangsu Zhengrui Taibang Electronics Co., Ltd.

[0137] (3) Oxygen index

[0138] According to GB / T 2406.2-2009, the sample size is prepared according to the type IV sample. The test is carried out according to method A-top surface ignition method. The test is carried out using the oxygen index tester device of Nanjing Jiangning District Fangshang Analytical Instrument Equipment Factory.

[0139] (4) Tensile strength and elongation at break

[0140] The test was conducted in accordance with Article 9 of GB 1040-2008, the test temperature was 23±2℃, and the tensile test used a standard dumbbell-shaped specimen with a tensile speed of 250mm / min. The tensile strength and elongation at break of 5 specimens were tested using a micro-controlled electronic universal material tensile machine from Dongguan High-speed Railway Testing Co., Ltd., and the results were averaged.

[0141] (5) 110-150℃ thermal shock

[0142] The test was carried out in accordance with Appendix A of GB / T 32129-2015, with a test temperature of 23±2°C and a weight of 2kg. Three samples were tested at each temperature using the thermal shock test device of Hebei Zhongke Beigong Testing Instrument Co., Ltd.

[0143] (6) Pants tear

[0144] According to GB / T 3917.2-2009 standard, the test is carried out. After cutting the sample according to the specified size, the two legs of the trouser-shaped sample are clamped so that the cut line of the sample is straight between the two clamps. Turn on the instrument and apply tension in the cut direction. Record the tear strength until it is torn to the specified length, calculate the average of the highest peak and the lowest peak in the specified area, and measure the tear strength.

[0145] The test results are shown in Table 3.

[0146] Embodiment 1:

[0147] 2 mol of aminopropyl heptaisobutyl caged polysilsesquioxane was dissolved in 100 ml of tetrahydrofuran solution, 0.2 mol of acetic acid catalyst was added to the solution, and 1 mol of benzo[B]naphtho[2,3-D]furan-2-hydroxyboric acid was added under stirring. The reaction was stirred for 2-4 hours, and the reaction was stopped, vacuum rotary evaporation was performed, water was added for washing, and drying was performed to obtain a modified POSS flame retardant synergist 1;

[0148] 22 parts of PP, 30 parts of SEBS, 30 parts of white oil, 8 parts of PE grafted maleic anhydride, 10 parts of modified POSS flame retardant synergist 1, 10 parts of aluminum diethylphosphinate, 10 parts of MCA flame retardant, 10 parts of aluminum hydroxide, 0.5 parts of lubricant, 0.5 parts of antioxidant and 0.3 parts of light stabilizer are mixed evenly, and granulated by twin-screw extrusion at 180°C to obtain a thermoplastic elastomer preform, and then dried at 80°C to obtain a highly flame retardant, crack-resistant and halogen-free thermoplastic elastomer material.

[0149] Embodiment 2:

[0150] The preparation method is the same as that of Example 1, except that:

[0151] 15 parts of PP, 20 parts of SEBS, 20 parts of white oil, 3 parts of PE grafted maleic anhydride, 15 parts of modified POSS flame retardant synergist 1, 15 parts of aluminum diethylphosphinate, 10 parts of MCA flame retardant, 12 parts of aluminum hydroxide, 0.5 parts of lubricant, 0.5 parts of antioxidant and 0.3 parts of light stabilizer are mixed evenly, and granulated by twin-screw extrusion at 180°C to obtain a thermoplastic elastomer preform, and then dried at 80°C to obtain a highly flame retardant, crack-resistant and halogen-free thermoplastic elastomer material.

[0152] Embodiment 3:

[0153] The preparation method is the same as that of Example 1, except that:

[0154] 22 parts of PP, 30 parts of SEBS, 30 parts of white oil, 8 parts of PE grafted maleic anhydride, 2 parts of modified POSS flame retardant synergist 1, 10 parts of aluminum diethylphosphinate, 25 parts of MCA flame retardant, 12 parts of aluminum hydroxide, 0.5 parts of lubricant, 0.5 parts of antioxidant and 0.3 parts of light stabilizer are mixed evenly, and granulated by twin-screw extrusion at 180°C to obtain a thermoplastic elastomer preform, and then dried at 80°C to obtain a highly flame retardant, crack-resistant and halogen-free thermoplastic elastomer material.

[0155] Embodiment 4:

[0156] The preparation method is the same as that of Example 1, except that:

[0157] 20 parts of PP, 25 parts of SEBS, 25 parts of white oil, 5 parts of PE grafted maleic anhydride, 10 parts of modified POSS flame retardant synergist 1, 15 parts of aluminum diethylphosphinate, 20 parts of MCA flame retardant, 15 parts of aluminum hydroxide, 0.5 parts of lubricant, 0.5 parts of antioxidant and 0.3 parts of light stabilizer are mixed evenly, and granulated by twin-screw extrusion at 180°C to obtain a thermoplastic elastomer preform, and then dried at 80°C to obtain a highly flame retardant, crack-resistant and halogen-free thermoplastic elastomer material.

[0158] Embodiment 5:

[0159] The preparation method is the same as that of Example 1, except that:

[0160] 18 parts of PP, 22 parts of SEBS, 22 parts of white oil, 5 parts of PE grafted maleic anhydride, 12 parts of modified POSS flame retardant synergist 1, 25 parts of diethyl aluminum phosphinate, 20 parts of MCA flame retardant, 15 parts of aluminum hydroxide, 0.5 parts of lubricant, 0.5 parts of antioxidant and 0.3 parts of light stabilizer are mixed evenly, and granulated by twin-screw extrusion at 180°C to obtain a thermoplastic elastomer preform, and then dried at 80°C to obtain a highly flame retardant, crack-resistant and halogen-free thermoplastic elastomer material.

[0161] Embodiment 6:

[0162] The preparation method is the same as that of Example 1, except that:

[0163] 22 parts of PP, 30 parts of SEBS, 30 parts of white oil, 8 parts of PE grafted maleic anhydride, 15 parts of modified POSS flame retardant synergist 1, 15 parts of diethyl aluminum phosphinate, 15 parts of MCA flame retardant, 12 parts of aluminum hydroxide, 0.5 parts of lubricant, 0.5 parts of antioxidant and 0.3 parts of light stabilizer are mixed evenly, and granulated by twin-screw extrusion at 180°C to obtain a thermoplastic elastomer preform, and then dried at 80°C to obtain a highly flame retardant, crack-resistant and halogen-free thermoplastic elastomer material.

[0164] Embodiment 7:

[0165] The preparation method is the same as that of Example 1, except that:

[0166] 18 parts of PP, 22 parts of SEBS, 22 parts of white oil, 5 parts of PE grafted maleic anhydride, 15 parts of modified POSS flame retardant synergist 1, 15 parts of aluminum diethylphosphinate, 15 parts of MCA flame retardant, 12 parts of aluminum hydroxide, 0.5 parts of lubricant, 0.5 parts of antioxidant and 0.3 parts of light stabilizer are mixed evenly, and granulated by twin-screw extrusion at 180°C to obtain a thermoplastic elastomer preform, and then dried at 80°C to obtain a highly flame retardant, crack-resistant and halogen-free thermoplastic elastomer material.

[0167] Embodiment 8:

[0168] The preparation method is the same as that of Example 1, except that:

[0169] 18 parts of PP, 22 parts of SEBS, 22 parts of white oil, 5 parts of PE grafted maleic anhydride, 12 parts of modified POSS flame retardant synergist 1, 12 parts of aluminum diethylphosphinate, 12 parts of MCA flame retardant, 12 parts of aluminum hydroxide, 0.5 parts of lubricant, 0.5 parts of antioxidant and 0.3 parts of light stabilizer are mixed evenly, and granulated by twin-screw extrusion at 180°C to obtain a thermoplastic elastomer preform, and then dried at 80°C to obtain a highly flame retardant, crack-resistant and halogen-free thermoplastic elastomer material.

[0170] Embodiment 9:

[0171] The preparation method is the same as that of Example 1, except that:

[0172] 18 parts of PP, 22 parts of SEBS, 22 parts of white oil, 5 parts of PE grafted maleic anhydride, 12 parts of modified POSS flame retardant synergist 1, 20 parts of aluminum diethylphosphinate, 4 parts of MCA flame retardant, 12 parts of aluminum hydroxide, 0.5 parts of lubricant, 0.5 parts of antioxidant and 0.3 parts of light stabilizer are mixed evenly, and granulated by twin-screw extrusion at 180°C to obtain a thermoplastic elastomer preform, and then dried at 80°C to obtain a highly flame retardant, crack-resistant and halogen-free thermoplastic elastomer material.

[0173] Embodiment 10:

[0174] 2 mol of aminopropyl heptaisobutyl caged polysilsesquioxane was dissolved in 100 ml of tetrahydrofuran solution, 0.2 mol of acetic acid catalyst was added to the solution, and 1 mol of dibenzofuran-3-boric acid was added under stirring. The reaction was stirred for 2-4 hours, and the reaction was stopped. The mixture was evaporated under reduced pressure, washed with water, and dried to obtain the modified POSS flame retardant synergist 2.

[0175] 18 parts of PP, 22 parts of SEBS, 22 parts of white oil, 5 parts of PE grafted maleic anhydride, 12 parts of modified POSS flame retardant synergist 2, 4 parts of diethyl aluminum phosphinate, 20 parts of MCA flame retardant, 12 parts of aluminum hydroxide, 0.5 parts of lubricant, 0.5 parts of antioxidant and 0.3 parts of light stabilizer are mixed evenly, and granulated by twin-screw extrusion at 180°C to obtain a thermoplastic elastomer preform, and then dried at 80°C to obtain a highly flame retardant, crack-resistant and halogen-free thermoplastic elastomer material.

[0176] Comparative Example 1:

[0177] The preparation method is the same as that of Example 1, except that:

[0178] 18 parts of PP, 22 parts of SEBS, 22 parts of white oil, 5 parts of PE grafted maleic anhydride, 18 parts of modified POSS flame retardant synergist 1, 12 parts of aluminum diethylphosphinate, 12 parts of MCA flame retardant, 12 parts of aluminum hydroxide, 0.5 parts of lubricant, 0.5 parts of antioxidant and 0.3 parts of light stabilizer are mixed evenly, and granulated by twin-screw extrusion at 180°C to obtain a thermoplastic elastomer preform, and then dried at 80°C to obtain a highly flame retardant, crack-resistant and halogen-free thermoplastic elastomer material.

[0179] Comparative Example 2:

[0180] 18 parts of PP, 22 parts of SEBS, 22 parts of white oil, 5 parts of PE grafted maleic anhydride, 16 parts of aluminum diethylphosphinate, 16 parts of MCA flame retardant, 16 parts of aluminum hydroxide, 0.5 parts of lubricant, 0.5 parts of antioxidant, and 0.3 parts of light stabilizer were mixed evenly, and granulated by twin-screw extrusion at 180°C to obtain a thermoplastic elastomer preform, and then dried at 80°C to obtain a highly flame-retardant, crack-resistant, and halogen-free thermoplastic elastomer material. Comparative Example 3:

[0181] The preparation method is the same as that of Example 1, except that:

[0182] 18 parts of PP, 22 parts of SEBS, 22 parts of white oil, 5 parts of PE grafted maleic anhydride, 12 parts of modified POSS flame retardant synergist 1, 24 parts of MCA flame retardant, 12 parts of aluminum hydroxide, 0.5 parts of lubricant, 0.5 parts of antioxidant and 0.3 parts of light stabilizer are mixed evenly, and granulated by twin-screw extrusion at 180°C to obtain a thermoplastic elastomer preform, and then dried at 80°C to obtain a highly flame retardant, crack-resistant and halogen-free thermoplastic elastomer material.

[0183] Comparative Example 4:

[0184] The preparation method is the same as that of Example 1, except that:

[0185] 18 parts of PP, 22 parts of SEBS, 22 parts of white oil, 5 parts of PE grafted maleic anhydride, 12 parts of modified POSS flame retardant synergist 1, 24 parts of aluminum diethylphosphinate, 12 parts of aluminum hydroxide, 0.5 parts of lubricant, 0.5 parts of antioxidant and 0.3 parts of light stabilizer are mixed evenly, and granulated by twin-screw extrusion at 180°C to obtain a thermoplastic elastomer preform, and then dried at 80°C to obtain a highly flame retardant, crack-resistant and halogen-free thermoplastic elastomer material.

[0186] Comparative Example 5:

[0187] The preparation method is the same as that of Example 10, except that:

[0188] 18 parts of PP, 22 parts of SEBS, 22 parts of white oil, 5 parts of PE grafted maleic anhydride, 48 parts of modified POSS flame retardant synergist 1, 0.5 parts of lubricant, 0.5 parts of antioxidant and 0.3 parts of light stabilizer are mixed evenly, and granulated by twin-screw extrusion at 180°C to obtain a thermoplastic elastomer preform, and then dried at 80°C to obtain a highly flame retardant, crack-resistant and halogen-free thermoplastic elastomer material.

[0189] Comparative Example 6:

[0190] 18 parts of PP, 22 parts of SEBS, 22 parts of white oil, 5 parts of PE grafted maleic anhydride, 48 parts of diethyl aluminum phosphinate, 0.5 parts of lubricant, 0.5 parts of antioxidant and 0.3 parts of light stabilizer are mixed evenly, and granulated by twin-screw extrusion at 180°C to obtain a thermoplastic elastomer preform, and then dried at 80°C to obtain a highly flame-retardant, crack-resistant and halogen-free thermoplastic elastomer material.

[0191] Comparative Example 7:

[0192] 18 parts of PP, 22 parts of SEBS, 22 parts of white oil, 5 parts of PE grafted maleic anhydride, 48 parts of aluminum hydroxide, 0.5 parts of lubricant, 0.5 parts of antioxidant and 0.3 parts of light stabilizer are mixed evenly, and granulated by twin-screw extrusion at 180°C to obtain a thermoplastic elastomer preform, and then dried at 80°C to obtain a highly flame-retardant, crack-resistant and halogen-free thermoplastic elastomer material.

[0193] Comparative Example 8:

[0194] 18 parts of PP, 22 parts of SEBS, 22 parts of white oil, 5 parts of PE grafted maleic anhydride, 12 parts of benzo[B]naphtho[2,3-D]furan-2-hydroxyboric acid flame retardant, 12 parts of aluminum diethylphosphinate, 12 parts of MCA flame retardant, 12 parts of aluminum hydroxide, 0.5 parts of lubricant, 0.5 parts of antioxidant and 0.3 parts of light stabilizer are mixed evenly, granulated by twin-screw extrusion at 180°C to obtain a thermoplastic elastomer preform, and then dried at 80°C to obtain a highly flame-retardant, crack-resistant and halogen-free thermoplastic elastomer material.

[0195] Comparative Example 9:

[0196] 18 parts of PP, 22 parts of SEBS, 22 parts of white oil, 5 parts of PE grafted maleic anhydride, 12 parts of aminopropyl heptaisobutyl caged polysilsesquioxane flame retardant, 12 parts of aluminum diethylphosphinate, 12 parts of MCA flame retardant, 12 parts of aluminum hydroxide, 0.5 parts of lubricant, 0.5 parts of antioxidant and 0.3 parts of light stabilizer are mixed evenly, granulated by twin-screw extrusion at 180°C to obtain a thermoplastic elastomer preform, and then dried at 80°C to obtain a highly flame-retardant, crack-resistant and halogen-free thermoplastic elastomer material.

[0197] Comparative Example 10:

[0198] 18 parts of PP, 22 parts of SEBS, 22 parts of white oil, 5 parts of PE grafted maleic anhydride, 6 parts of benzo[B]naphtho[2,3-D]furan-2-hydroxyboric acid flame retardant, 6 parts of aminopropyl heptaisobutyl caged polysilsesquioxane flame retardant, 12 parts of aluminum diethylphosphinate, 12 parts of MCA flame retardant, 12 parts of aluminum hydroxide, 0.5 parts of lubricant, 0.5 parts of antioxidant and 0.3 parts of light stabilizer are mixed evenly, granulated by twin-screw extrusion at 180°C to obtain a thermoplastic elastomer preform, and then dried at 80°C to obtain a highly flame-retardant, crack-resistant and halogen-free thermoplastic elastomer material.

[0199] Comparative Example 11:

[0200] 2 mol of aminopropyl heptaisobutyl caged polysilsesquioxane was dissolved in 100 ml of tetrahydrofuran solution, 0.2 mol of acetic acid catalyst was added to the solution, and 1 mol of methylboric acid was added under stirring. The reaction was stirred for 2-4 hours, and the reaction was stopped, vacuum rotary evaporation was performed, water was added for washing, and drying was performed to obtain methylboric acid modified POSS flame retardant.

[0201] 18 parts of PP, 22 parts of SEBS, 22 parts of white oil, 5 parts of PE grafted maleic anhydride, 12 parts of methyl boric acid modified POSS flame retardant, 2 parts of diethyl aluminum phosphinate, 12 parts of MCA flame retardant, 12 parts of aluminum hydroxide, 0.5 parts of lubricant, 0.5 parts of antioxidant and 0.3 parts of light stabilizer are evenly mixed, granulated by twin-screw extrusion at 180°C to obtain a thermoplastic elastomer preform, and then dried at 80°C to obtain a highly flame-retardant, crack-resistant and halogen-free thermoplastic elastomer material.

[0202] Comparative Example 12:

[0203] 2 mol of aminopropyl heptaisobutyl caged polysilsesquioxane was dissolved in 100 ml of tetrahydrofuran solution, 0.2 mol of acetic acid catalyst was added to the solution, and 1 mol of phenylboric acid was added under stirring. The reaction was stirred for 2-4 hours, and the reaction was stopped, vacuum rotary evaporation was performed, water was added for washing, and drying was performed to obtain phenylboric acid modified POSS flame retardant.

[0204] 18 parts of PP, 22 parts of SEBS, 22 parts of white oil, 5 parts of PE grafted maleic anhydride, 12 parts of phenylboric acid modified POSS flame retardant, 2 parts of diethyl aluminum phosphinate, 12 parts of MCA flame retardant, 12 parts of aluminum hydroxide, 0.5 parts of lubricant, 0.5 parts of antioxidant and 0.3 parts of light stabilizer are mixed evenly, and granulated by twin-screw extrusion at 180°C to obtain a thermoplastic elastomer preform, and then dried at 80°C to obtain a highly flame-retardant, crack-resistant and halogen-free thermoplastic elastomer material.

[0205] The components and important preparation variables of Examples 1-10 and Comparative Examples 1-12 are summarized in Table 2. Table 2 Components of Examples 1-10 and Comparative Examples 1-12 of the present invention.

[0206] Table 2 Examples of the present invention and comparative examples

[0207]

[0208]

[0209] According to the provisions of GB / T 1040-2008, GB / T 5455, GB / T 2406.2, GB / T32129, UL94 and GB / T3917.2-2009, the thermoplastic elastomer materials in the above Examples 1-10 and Comparative Examples 1-12 were tested for tensile strength, elongation at break, flame retardancy, oxygen index, 110°C heat shock, 130°C heat shock, 150°C heat shock, dripping during burning and trouser-type tearing, and the test results were recorded in the following Table 3:

[0210] Table 3 Performance test table of Examples 1-10 of the present invention and Comparative Examples 1-12

[0211]

[0212]

[0213] According to Table 3, it can be seen that the thermoplastic elastomer injection molded sheets of Examples 1-9 have high flame retardancy, and the flame retardancy grades all reach V0 grade, and the V0 grade test does not drip, and the oxygen index is >25. The number of parts of the N-series flame retardant in Example 9 is 4 parts, and its physical and mechanical properties are reduced relative to Example 8. The number of parts of the P-series flame retardant in Example 10 is 4 parts, and the flame retardancy grade in Example 10 is V1 relative to Example 8, indicating that the flame retardancy is reduced. It can be seen that the modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist has a synergistic flame retardant effect with the P-series flame retardant and the N-series flame retardant, which can further improve the flame retardancy and physical and mechanical properties of the thermoplastic elastomer injection molded sheet. In Comparative Examples 2, 6 and 7, no modified POSS flame retardant synergist is added. Compared with Example 8, all three show dripping during the combustion process, and the flame retardant properties of the three are poor. Among them, the samples of Comparative Examples 6 and 7 show cracking in the 110°C thermal shock test, the 130°C thermal shock test, and the 150°C thermal shock test, indicating that the modified POSS flame retardant synergist, the P series flame retardant and the N series flame retardant in the present invention need to work together. During the combustion process, the Si element can react rapidly with the C element in the R2 group to generate a large number of Si-C bonds. At the same time, the B element can form a glass film on the surface of the thermoplastic polyester elastomer material, and the generated boric acid rapidly dehydrates the polymer to produce a carbon layer. The B element in the modified POSS synergistic flame retardant can also coordinate with the P element in the system to produce a synergistic effect, thereby improving the flame retardant effect, while the P series flame retardant provides an acid source, the N series flame retardant provides a gas source, and the modified POSS synergistic flame retardant provides a rich carbon source, so that the P series flame retardant and the N series flame retardant exert stronger flame retardancy, and the three work together to achieve the excellent flame retardancy, physical and mechanical properties, anti-drip and thermal shock resistance of thermoplastic elastomer materials. It can be seen from Example 8 and Comparative Example 8 that the polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist have better anti-drip performance than benzo[B]naphtho[2,3-D]furan-2-hydroxyboric acid flame retardant. It can be seen from Example 8 and Comparative Example 9 that the flame retardant and anti-drip performance of the polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist are better than the aminopropyl heptaisobutyl caged polysilsesquioxane flame retardant. It can be seen from Example 8 and Comparative Example 10 that the flame retardant synergist of polyhedral oligomeric silsesquioxane and its derivatives has better anti-drip performance than the flame retardant mixed with aminopropyl heptaisobutyl caged polysilsesquioxane and benzo[B]naphtho[2,3-D]furan-2-hydroxyboric acid. It can be seen from Example 8 and Comparative Examples 11 and 12 that the flame retardant synergist of polyhedral oligomeric silsesquioxane and its derivatives of the present invention has better flame retardant and anti-drip performance than other polyhedral oligomeric silsesquioxane flame retardants containing boric acid modification such as benzofuran groups and polycyclic aromatic groups, thereby indicating that the flame retardant synergist of polyhedral oligomeric silsesquioxane and its derivatives of the present invention has excellent flame retardant and anti-drip performance.

[0214] Therefore, the present invention verifies that the flame retardancy of thermoplastic elastomer materials is improved by modifying the POSS flame retardant synergist, so that the materials have excellent physical and mechanical properties and excellent combustion and dripping prevention effects, and thus have extremely high industrial value and can be widely used and promoted.

[0215] The above are only preferred embodiments of the present invention, and do not limit the patent scope of the present invention. For those skilled in the art, the present invention may have various changes and modifications. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the patent protection scope of the present invention.

Claims

1. A thermoplastic elastomer material, characterized in that: The raw materials of the thermoplastic elastomer material include, by weight: PP 15-22 parts, SEBS 20-30 parts, 20-30 parts of plasticizer, 3-8 parts of compatibilizer, P series flame retardant 10-25 parts, N series flame retardant 10-25 parts, Inorganic flame retardant 10-15 parts, 2-15 parts of modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist, Wherein, the structure of the modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist is: Wherein, R is a non-reactive group, such as isobutyl, isooctyl, ethyl, cyclohexyl, cyclopentyl, or phenyl, and R1 is n-propyl or phenylene; R2 is a cyclic structure with a carbon-to-hydrogen ratio greater than 1, including at least one of a benzofuran group and a polycyclic aromatic group.

2. The thermoplastic elastomer material according to claim 1, characterized in that The benzofuran group includes at least one of a benzofuran group and a dibenzofuran group; And / or, the polycyclic aromatic group includes at least one of a naphthalene ring group, an anthracene ring group, a phenanthrene ring group, an acenaphthene ring group, a fluorene ring group and a perylene ring group.

3. The thermoplastic elastomer material according to claim 1, characterized in that The modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist is prepared by dehydration reaction of compound 1 and compound 2 under the action of a catalyst, and the reaction route is as follows:

4. The thermoplastic elastomer material according to claim 3, characterized in that The molar ratio of compound 1 to compound 2 is 2:

1.

5. The thermoplastic elastomer material according to claim 3, characterized in that The preparation method of the modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist comprises the following steps: Dissolving compound 1 in an organic solvent, adding an aqueous solution of compound 2 under the action of a catalyst, performing a catalytic reaction, and then washing and drying to obtain the modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist; Wherein, the organic solvent includes at least one of alcohols, aromatic hydrocarbons, aliphatic hydrocarbons, alicyclic hydrocarbons, ethers, ketones and diol derivatives; The catalyst includes at least one of an acidic catalyst, a metal catalyst, and a basic catalyst.

6. The thermoplastic elastomer material according to claim 1, characterized in that The raw materials of the thermoplastic elastomer material include, by weight: PP 15-22 parts, SEBS 20-30 parts, 20-30 parts of plasticizer, 3-8 parts of compatibilizer, P series flame retardant 10-15 parts, N series flame retardant 10-15 parts, Inorganic flame retardant 10-12 parts, 2-15 parts of modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist.

7. The thermoplastic elastomer material according to claim 1, characterized in that The plasticizer includes at least one of white oil, naphthenic oil and paraffin oil.

8. The thermoplastic elastomer material according to claim 1, characterized in that The compatibilizer includes at least one of PE grafted maleic anhydride, POE grafted maleic anhydride, PP grafted maleic anhydride, and EMA grafted maleic anhydride.

9. The thermoplastic elastomer material according to claim 1, characterized in that The P series flame retardant includes an inorganic phosphorus flame retardant or an organic phosphorus flame retardant, wherein the inorganic phosphorus flame retardant includes at least one of red phosphorus, phosphate, and polyphosphate; the organic phosphorus flame retardant includes at least one of phosphate, phosphite, and phosphine oxide; And / or, the N series flame retardant includes at least one of melamine urate, melamine phosphate, and melamine inorganic acid salt.

10. The thermoplastic elastomer material according to claim 1, characterized in that The inorganic flame retardant includes at least one of magnesium hydroxide, aluminum hydroxide and calcium carbonate.

11. The thermoplastic elastomer material according to claim 1, characterized in that The raw materials of the thermoplastic elastomer material also include at least one of a lubricant, an antioxidant, and a light stabilizer; wherein, in terms of weight parts, the lubricant is 0.2-1 parts, the antioxidant is 0.5-2 parts, and the light stabilizer is 0.2-1 parts.

12. A method for preparing a thermoplastic elastomer material according to claim 1, characterized in that: The method comprises the following steps: mixing the raw materials uniformly, extruding and granulating through an extruder, and obtaining granular materials, namely the thermoplastic elastomer material.

13. The method for preparing a thermoplastic elastomer material according to claim 11, characterized in that: The raw materials also include at least one of a lubricant, an antioxidant, and a light stabilizer.

Citation Information

Patent Citations

  • Low-dielectric high-melt-strength flame-retardant polypropylene material and preparation method thereof

    CN112063048A

  • Multi-element integrated flame retardant containing Schiff base structure and flame-retardant polyester prepared from multi-element integrated flame retardant

    CN116854916A

  • Phosphate modified POSS (polyhedral oligomeric silsesquioxane) flame retardant, TPS (thermoplastic polystyrene) sheath material, preparation method of TPS sheath material and sheath

    CN117887080A

  • Novel TPE material and preparation method thereof

    CN118359917A

  • Intumescent, flame-retardant and functionalized POSS flame retardant and preparation method therefor

    WO2023109737A1